Decentralized P2P power trading mechanism for dynamic multi-energy microgrid groups based on priority matching. (November 2022) - Chen, Yanxu; Lei, Xia; Yang, Jian; Zhong, Hongming; Huang, Tao
Abstract: In order to promote the interaction among interconnected microgrids (MGs) with multiply distributed energy resources (DERs) to local energy utilization, a decentralized peer-to-peer (P2P) power trading mechanism based on priority matching is proposed. The priority indices are calculated based on scheduling results and quotations by an independent MG operator (IMO), which protect effectively the privacy and represent the bargaining willingness of MGs. According to the supply–demand ratio within a matching pair, each MG is permitted to update its quotation multi-times until the convergence or updated number limitation is reached. The clearing price of each pair is calculated by the mid-market rate (MMR) method. Because the imbalanced power is different with the autonomous scheduling in a MG at different dispatching time, the different power requirements of MGs results in the formation of the dynamic MG groups. The simulation results in an interconnected multi-microgrid system (IMMGS) with 4 MGs show the proposed decentralized P2P mechanism is reasonable and effective.